(untitled) (Argos, 2025)
In the Oedipus Tyrannus Fourth Stasimon, the Chorus thinks about Oedipus’ life, expressing both his fidelity and thankfulness to the king. In a quiet tone, the elder men express a concentration of concepts interesting to review. The Chorus contributes with the compositional symmetry, since both Stasima, the Second as well as the Forth, concern to the play but are directed to the public. Both of them look at citizens. From this point of view, we make the philological-literary analysis of the Stasimon and relate to the co-text. At the same time, we inquire again at the thought of Sophocles.